Youth co-design of responsive digital badge systems: disrupting hierarchy and empowering youth. Issue 3 (3rd July 2021) - Tierney, Gavin; Horstman, Theresa; Tzou, Carrie
ABSTRACT: While digital badges were initially seen as valuable to educational programmes, critiques of digital badges focus on, among other things, the ways badges commodify learning. This paper proposes an alternative to overly simplified and commodified badges systems, which we refer to as responsive badge systems. We examine the history of digital badges in educational programmes and their relationship with commodification of learning. Analysis focuses on data from youth co-design of a responsive digital badge system in an informal learning environment. Results identify the design principles of a responsive badge system and examine variations in agency that youth experience during co-design.